Interplay between dietary intake, gut microbiota, and metabolic profile in obese adolescents: Sex-dependent differential patterns. Issue 12 (December 2022) - Liu, Yang; Chen, Lei; Liu, Lei; Zhao, Shan-Shan; You, Jun-Qiao; Zhao, Xin-Jie; Liu, Hui-Xin; Xu, Guo-Wang; Wen, De-Liang
Summary: Background & aims: The interplay among dietary intake, gut microbiota, gut metabolites and circulating metabolites in adolescents is barely known, not to mention sex-dependent pattern. We aimed to explore unique profiles of gut bacterial, gut metabolites and circulating metabolites from both genders of adolescents due to BMI and eating pattern. Methods: Clinical indices, fecal gut microbiota, fecal and plasma metabolites, and diet intake information were collected in case–control sample matched for normal and obesity in girls (normal = 12, obesity = 12) and boys (normal = 20, obesity = 20), respectively. 16S rRNA gene sequencing and untargeted metabolomics was performed to analysis the signature of gut microbiota and metabolites. Unique profiles of girls associated with BMI and eating pattern was revealed by Spearman's correlations analysis, co-occurrence network analysis, Kruskal–Wallis test, and Wilcoxon rank-sum test. Results: Gender difference was found between normal and obese adolescents in gut microbiota, fecal metabolites, and plasma metabolites. The Parabacteroides were only decreased in obese girls. And the characteristic of obese girls' and boys' cases in fecal and plasma was xanthine and glutamine, ornithine and LCA, respectively. Soy products intake was negatively associated with Parabacteroides . The predicted model has a higher accuracy based on the combined markers in obesity boys (AUC = 0.97) and girls (AUC = 0.97), respectively. Conclusions: Reduced abundance of Phascolarctobacterium and Parabacteroides, as well as the increased fecal xanthine and ornithine, may provide a novel biomarker signature in obesity girls and boys. Soy products intake was positively and negatively associated with Romboutsia and Parabacteroides abundance, respectively. And the combined markers facilitate the accuracy of predicting obesity in girls and boys in advance.